Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1016/s0092-8674(00)80861-2
|View full text |Cite
|
Sign up to set email alerts
|

Tribbles Coordinates Mitosis and Morphogenesis in Drosophila by Regulating String/CDC25 Proteolysis

Abstract: Morphogenesis and cell differentiation in multicellular organisms often require accurate control of cell divisions. We show that a novel cell cycle regulator, tribbles, is critical for this control during Drosophila development. During oogenesis, the level of tribbles affects the number of germ cell divisions as well as oocyte determination. The mesoderm anlage enters mitosis prematurely in tribbles mutant embryos, leading to gastrulation defects. We show that Tribbles acts by specifically inducing degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
292
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 335 publications
(309 citation statements)
references
References 41 publications
11
292
1
Order By: Relevance
“…Trbl blocks mesoderm proliferation by directing turnover of String phosphatase, preventing activation of Cyclin/cdc2, perhaps to accommodate epithelial to mesenchymal cell shape changes incompatible with cell rounding that typically occurs during division. Close examination of trbl mutants reveals that excess cell proliferation occurs both earlier at blastoderm formation and later in both the migrating germ line pole cells and cells in the head (Mata et al, 2000;Seher and Leptin, 2000), indicating that in at least three embryonic tissues Trbl regulates cell division to promote cell migration (Duncan and Su, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trbl blocks mesoderm proliferation by directing turnover of String phosphatase, preventing activation of Cyclin/cdc2, perhaps to accommodate epithelial to mesenchymal cell shape changes incompatible with cell rounding that typically occurs during division. Close examination of trbl mutants reveals that excess cell proliferation occurs both earlier at blastoderm formation and later in both the migrating germ line pole cells and cells in the head (Mata et al, 2000;Seher and Leptin, 2000), indicating that in at least three embryonic tissues Trbl regulates cell division to promote cell migration (Duncan and Su, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…C,D: In Xenopus, antisense morpholino knockdown of Xtrib2 (D) leads to defects in neural tube closure, with delayed infolding (black arrows, D) documented by expression of the Xenopus Slug gene (XSlu) when compared with normal gastrulation following injection of a mutated morpholino (C). (A,B) from Mata et al (2000) and (C,D) from Saka and Smith (2004), with permissions, with permissions from the respective publishers. migration and division.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The Tribbles family of pseudokinases was first described in Drosophila as a negative regulator of cell division in early embryogenesis. [4][5][6][7] There are three mammalian Tribbles isoforms (Trib1, Trib2 and Trib3), homologs to the Drosophila tribbles proteins, and they all share a highly conserved central kinase-like domain, which lacks catalytic residues, and a 'tribbles specific' C-terminal domain, which has been proposed to participate in the binding to different Tribbles partners. 8 Tribbles pseudokinase-3 (TRIB3; also named TRB3, NIPK and SKIP3) has been proposed to interact with several proteins, including the transcription factors activating transcription factor 4 (ATF-4) and CHOP 9 as well as with several MAPKs.…”
mentioning
confidence: 99%
“…Tribbles proteins were first discovered in Drosophila as a negative regulator of string/cdc25, where when over-expressed directly inhibited mitosis (Grosshans and Wieschaus 2000). Simultaneously, TRIBs were found to promote the degradation of string via the proteasome pathway and showed that overexpression of tribbles in imaginal disc cells blocked the cell cycle at G2 resulting in abnormal wing morphology (Mata, et al 2000). Since then three highly conserved mammalian homologues have been indentified; Trib1, Trib2 and Trib3.…”
Section: Identitymentioning
confidence: 99%